Probing the importance of clonality: Single cell subcloning of clonally derived CHO cell lines yields widely diverse clones differing in growth, productivity, and product quality. (27th December 2017) - Ko, Peggy; Misaghi, Shahram; Hu, Zhilan; Zhan, Dejin; Tsukuda, Joni; Yim, Mandy; Sanford, Mark; Shaw, David; Shiratori, Masaru; Snedecor, Brad; Laird, Michael; Shen, Amy
Abstract : In the past few decades, a large variety of therapeutic antibodies and proteins have been expressed in Chinese hamster ovary (CHO) cells. This mammalian expression system is robust, scalable, relatively inexpensive, and importantly allows for post‐translational modifications that are important for some therapeutic proteins. Historically, CHO cell lines were derived from colonies of cells grown in semi‐solid or liquid plates using either serum‐containing or serum‐free media. Current advancements in cell sorting and imaging technologies have allowed for isolating and imaging single cell progenitors at the seeding step, significantly increasing the probability of isolating clonally derived cell lines. However, it is debatable how much population heterogeneity can be eliminated when clonally derived cell lines, originated from a single cell progenitor, are scaled up. To further investigate this phenomenon, we subcloned two different clonally derived (day 0 imaged and visually inspected) cell lines expressing antibody‐X. The results showed that when six randomly chosen subclones of each line were evaluated in a production assay, these subclones displayed a range of variation in titer, specific productivity, growth, and product quality attributes. Some subclones displayed variations in transgene copy numbers. Additionally, clonal derivation did not assure stability of the derived cell lines. Our findings show that cell heterogeneity exists in a population even when derived from a single cell progenitor. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 34:624–634, 2018